(3bGYOI eTQhYjI GdOdjd GdLfGFj (B: s (3OQGSI ebGQfI (B/ s - (3YGOd YHOGdHOjY BOe MSjfs; (3YGOd jMji bQfj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3jOhQ ehVhY OQGSJfG aj gPG GdHMK Mhd hGMOI ef Cge GdhSGFd GdELQGFjI GdJj jfXegG bGfhf GdELQGAGJ GdLfGFjI dMeGjI Mbhb GdEfSGf hMQjGJg GdCSGSjI(B: (3gPg GdhSjdI gj bGYOI eTQhYjI GdOdjd GdLfGFj(B: (3OQGSI ebGQfI Hjf GdTQjYI GdESdGejI hGdbGfhf GdeUQj hHYV GdbhGfjf GdhVYjI GdCNQi(B. (3hEf eG dgPg GdOQGSI ef CgejI(B: (3EfeG eQLYgG Edi SHHjf QFjSjjf; GdChd(B: (3Ef bGYOI eTQhYjI GdOdjd GdLfGFj JeKd VeGfI gGeI ef VeGfGJ Mbhb GdEfSGf hMQjGJg GdCSGSjI(B: (3CeG GdSHH GdKGfj aeDOGg(B: (3GdJbOe GdYdej hGdJcfhdhLj GdMOjK hCKQg aj GdEKHGJ GdLfGFj(B. (3hJJMOO CgOGa Jdc GdOQGSI GfWdGbkG ef YfhGfgG aj gOajf; eaGO GdChd(B: (3Gdhbha Ydi MbjbI GdeGgjI GdbGfhfjI dbGYOI eTQhYjI GdOdjd GdLfGFj(B: (3hPdc dHjGf eaghegG hVhGHWgG hJMOjO CQcGfgG hfWGbgG(B. (3heDOi GdKGfj(B: (3JMOjO GdBKGQ GdbGfhfjI dgPg GdbGYOI Ydi GdELQGAGJ GdeGSI HGdMQjI GdTNUjI Ydi GdCOdI GdeSJeOI ef GSJNOGe GdhSGFd GdYdejI GdMOjKI(B: (3hHjGf GdLRGA GdeJQJH Ydi GdENdGd HJdc GdbGYOIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2014(3, bSe GdbGfhf GdLfGFjs
(3HHdjhLQGajG(B: (3UaMGJ (B796-866s
Keywords: (3GdeTQhYjI GdLfGFjIs; (3GdELQGAGJ GdLfGFjI s; (3HQGAI GdeJges; (3GdEKHGJ GdLfGFjs; (3GdQbGHI GdbVGFjIs; (3VeGf GdMQjI GdTNUjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs